Microplastics in sea ice drifted to the Shiretoko Peninsula, the southern end of the Sea of Okhotsk - Hiroshi Ohno; Yoshinori Iizuka (Scientific Reports)
Abstract Sea ice is regarded as a temporal sink and carrier of microplastics (MPs). Nevertheless, knowledge and understanding of MPs in sea ice remain sparse. This study investigated the abundance, composition, size (> 30 μm), and shape of MPs in four sea-ice cores retrieved at the southern end of the Sea of Okhotsk. Nine microplastic (MP) types, mostly with fragmentary shapes, were detected among ice-core sections. Most fragmentary MPs were smaller than 120 μm, but all fiber MPs were in the largest size class (> 210 μm). MP concentrations were 0–60 particles/L, with an average of 21 particles/L. Higher occurrences of MPs observed in the lower ice layers are attributable to heavier MP contamination in the southern part of the sea and/or relocation of MPs in the ice matrix. No significant correlation was found between the distributions of MP and inorganic particle (sediment) abundances, implying difference in their kinetics of suspension freezing. Taken together, these findings suggest important implications for elucidating the nature and distribution of MPs in sea ice.